KOMUNIKASI PREVENTIF PEMERINTAH DAN KOMPONEN BANGSA LAIN DALAM MENINGKATKAN KESADARAN GENERASI Z MENUJU PERCEPATAN PENANGANAN COVID-19 (STUDI KUALITATIF PADA MAHASISWA DI PALANGKA RAYA): PREVENTIVE COMMUNICATIONS OF THE GOVERNMENT AND OTHER NATIONS COMPONENTS IN INCREASING GENERATION Z AWARENESS TOWARDS THE ACCELERATION OF COVID-19 HANDLING (QUALITATIVE STUDY ON STUDENTS IN PALANGKA RAYA) - Hayat, Muzahid Akbar; Ayuni, Risa Dwi; Sanusi, Sanusi (Anterior Jurnal, 2023)
This study discusses the role of preventif communication between the government and other components of the nation through the application of adaption of new habits in adolescent in an effort to accelerate the handling of COVID-19 againts the triggering factors, namely knowledge, attitudes of belief/belief, enabling factors; means infrasturture and factors driving the attitude and behavior of officers related to the implementation of the 5 (five) M health protocol. The research was conducted on students, the method used is descriptive qualitative research, with the sampling technique using purposive sampling. The number of informants is 10 (ten) men, aged 18-20 years. data sources are divided into three, namely: primary, secondary and tertiary data. Data collection techniques by means of observation, interviews, and documentation studies. Data analysis and data interpretation are looking at the role of preventive communication by the government and other components of the nation. Based on data analysis, it was found that of the 3 factors in their application, all of them have been applied. Only on the answer to when to replace the mask the answer is still diverse and not in accordance with the right concept.